KARTU REMI JAWA (KAREWA): STRATEGI EFEKTIF MENINGKATKAN MINAT ANAK DALAM PEMBELAJARAN AKSARA JAWA DENGAN SISTEM QUEEN CARD GAME - Azza Nurmalita; Trias Mira Hastuti; Tri Hardiyanti (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
This study aims to determine the effectiveness of using Kartu Remi Jawa (karewa) inlearning to read the Javanese alphabets through a Queen Card Game system.In this study an experimental method was employed. The data were collected throughpre test and post test. A group design was used to compare the results of the pre test andpost test. The class was also divided into an experimental class and a control class. Thetreatment to the experimental class was the use of Karewa media.The result of this study, the effectiveness of the use of Karewa in learning through playing,cannot be seen through the Independent T-Test because the control class has a very highvalue compared with the experimental value of the class. considering this, the researchersonly use Paired T-Test to see the effectiveness of using karewa. The effectiveness obtained is30%. Based on these results it is necessary to the determination of the experimental classand control classes with the same capacity (balanced), for example through tests givenbeforehand. Secondly, researchers should be able to hold a good control of both control andexperimental classes. Kartu Remi Jawa can be used as a medium of learning to enhancestudents’ interest in the Javanese alphabets. This will certainly have an impact on thepreservation of local culture in Java island.Key words: Kartu Remi Jawa (Karewa), interest in learning, Javanese alphabets, queen cardgame